Speech Act Analysis of O. Henry’s Short Stories and Implementation of the Integrated Teaching and Learning Process - Amanda Pradhani Yanwar (International Journal of Pedagogy and Teacher Education, 2020)
The teaching and learning process currently has an influence on students, especially the methods and the sources of the materials the teacher uses. The teacher can use various sources; for example, short stories, the use of which should be based on student needs. O. Henry’s short stories were analysed in this research as they are interesting and having moral values that can be useful for students. O. Henry was chosen because his short stories are suitable for the teaching and learning process. Classes of speech acts can be found in them: representatives, directives, commissives, expressives and declaratives. In the teaching and learning process, teachers need to integrate skills with each other. It is also explained in further detail how O. Henry’s short stories can be used to integrate reading and writing skills. Students need to integrate skills in order to be able to master them. In the paper, speech act analysis is made of O. Henry’s short stories and implementation of the integrated teaching and learning process is discussed.